The innovator's field guide : market tested methods and frameworks to help you meet your innovation challenges - Skarzynski, Peter; Crosswhite, David, 1961- (San Francisco, CA : Jossey-Bass, 2014)
'A step-by-step guide to successfully transforming any organization. It is well recognized that succeeding at innovation is fundamental in today's hyper-competitive global marketplace. It is the only way to outperform current and emerging competitors sustainably. But what we call'innovation' is messy and difficult and too often lacks the rigor and discipline of other management processes. The Innovator's Field Guide: Market Tested Methods and Frameworks to Help You Meet Your Innovation Challenges changes that. It is a practical guide that moves beyond the'why' to the'how' of making innovation happen, for leaders and practitioners inside organizations of all sizes.Written by two pioneers in the field of embedding innovation in organization, The Innovator's Field Guide focuses on the most pressing innovation problems and specific challenges innovation leaders will face and offers concrete solutions, tools, and methods to overcome them. Each chapter describes a specific innovation challenge and details proven ways to address that challenge Includes practical ideas, techniques, and leading practices Describes common obstacles and offers practical solutions Any leader or professional who needs concrete solutions--right now--to the critical challenges of innovation will find invaluable aid in the practical, easy-to-understand, and market-tested approaches of The Innovator's Field Guide'--
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Creative ability in business; New products